PENGARUH EKSPLAN DAN ZPT TERHADAP PERTUMBUHAN nEPEnTHES ALBOmARGInATA SECARA In VITRO - Sukamto, Lazarus Agus (Jurnal Teknologi Lingkungan, 2011)
Nepenthes albomarginata Lobb ex Lindl. is a carnivorous plant, distributes in several regions in Indonesia. The plant population decreases drastically because of over exploitation and ruining nature habitat. Plant propagation by nature and cutting are not enough to rehabilitation its population. In vitro culture of N. albomarginata was carried out using plantlets grown from the seeds in vitro. Plantlets were cut to became two part explants, consisted of shoot tip and under-shoot tip cuttings. These cutting explants were grown on Murashige & Skoog (MS) media with addition of plant growth regulators of 6-benzylaminopurine (BA), combined with or without-naphthalene acetic acid (NAA) or 2,4-dichlorophenoxyacetic acid (2,4-D) at 1 mg/l. Shoot tip cuttings of N. albomarginata formed double multiple shoot 25,00% on control; formed triple multiple shoots 25,00% onBA 1 mg/l treatment; formed callus 37,50%, triple or quartet shoots 25,00% and rooted plantlets 25,00% on BA 1 mg/l + NAA 1 mg/l treatment. The under-shoot tip cuttings ofN. albomarginata formed double – triple shoots 25,00% and rooted plantlets 37,50% on control; formed double – triple shoots 25,00% and rooted plantlets 12,50% on BA 1 mg/ltreatment; formed callus 12,50%, double - pentacle shoots 37,50% and rooted plantlets 25,00% on BA 1 mg/l + NAA 1 mg/l treatment. 2,4-D 1 mg/l or its combined with BA 1mg/l treatment caused deadly shoot tip or under-shoot tip explants. The combination of BA 1 mg/l + NAA 1 mg/l was the best treatment for producing callus, multiple shootsand rooted plantlets of N. albomarginata.